Integration of transcriptome and metabolome analyses reveals sorghum roots responding to cadmium stress through regulation of the flavonoid biosynthesis pathway - Jiao, Zhiyin; Shi, Yannan; Wang, Jinping; Wang, Zhifang; Zhang, Xing; Jia, Xinyue; Du, Qi; Niu, Jingtian; Liu, Bocheng; Du, Ruiheng; Ji, Guisu; Cao, Junfeng; et al. (Frontiers in Plant Science, 2023)
Cadmium (Cd) pollution is a serious threat to plant growth and human health. Although the mechanisms controlling the Cd response have been elucidated in other species, they remain unknown in Sorghum (Sorghum bicolor (L.) Moench), an important C4 cereal crop. Here, one-week-old sorghum seedlings were exposed to different concentrations (0, 10, 20, 50 100, and 150 μM) of CdCl2 and the effects of these different concentrations on morphological responses were evaluated. Cd stress significantly decreased the activities of the enzymes peroxidase (POD), superoxide dismutase (SOD), glutathione S-transferase (GST) and catalase (CAT), and increased malondialdehyde (MDA) levels, leading to inhibition of plant height, decreases in lateral root density and plant biomass production. Based on these results, 10 μM Cd concentration was chosen for further transcription and metabolic analyses. A total of 2683 genes and 160 metabolites were found to have significant differential abundances between the control and Cd-treated groups. Multi-omics integrative analysis revealed that the flavonoid biosynthesis pathway plays a critical role in regulating Cd stress responses in sorghum. These results provide new insights into the mechanism underlying the response of sorghum to Cd.